The teleost fish PepT1-type peptide transporters and their relationships with neutral and charged substrates - Vacca, Francesca; Gomes, Ana S.; De Gennaro, Marco; Rønnestad, Ivar; Bossi, Elena; Verri, Tiziano (Frontiers in Physiology, 2023)
In teleosts, two PepT1-type (Slc15a1) transporters, i.e., PepT1a and PepT1b, are expressed at the intestinal level. They translocate charged di/tripeptides with different efficiency, which depends on the position of the charged amino acid in the peptide and the external pH. The relation between the position of the charged amino acid and the capability of transporting the dipeptide was investigated in the zebrafish and Atlantic salmon PepT1-type transporters. Using selected charged (at physiological pH) dipeptides: i.e., the negatively charged Asp-Gly and Gly-Asp, and the positively charged Lys-Gly and Gly-Lys and Lys-Met and Met-Lys, transport currents and kinetic parameters were collected. The neutral dipeptide Gly-Gln was used as a reference substrate. Atlantic salmon PepT1a and PepT1b transport currents were similar in the presence of Asp-Gly and Gly-Asp, while zebrafish PepT1a elicited currents strongly dependent on the position of Asp in the dipeptide and zebrafish PepT1b elicited small transport currents. For Lys-and Met-containing dipeptides smaller currents compared to Gly-Gln were observed in PepT1a-type transporters. In general, for zebrafish PepT1a the currents elicited by all tested substrates slightly increased with membrane potential and pH. For Atlantic salmon PepT1a, the transport current increased with negative potential but only in the presence of Metcontaining dipeptides and in a pH-dependent way. Conversely, large currents were shown for PepT1b for all tested substrates but Gly-Lys in Atlantic salmon. This shows that in Atlantic salmon PepT1b for Lys-containing substrates the position of the charged dipeptides carrying the Lys residue defines the current amplitudes, with larger currents observed for Lys in the C-terminal position. Our results add information on the ability of PepT1 to transport charged amino acids and show species-specificity in the kinetic behavior of PepT1-type proteins. They also suggest the importance of the proximity of the substrate binding site of residues such as Lys PepT1a /Gln PepT1b for recognition and specificity of the charged dipeptide and point out the role of the comparative approach that exploits the natural protein variants to understand the structure and functions of membrane transporters.